Відприслівникові дієслівні аналітичні синтаксичні транспозити у формально-синтаксичній стріктурі простого речення - Мельник, Ірина; Melnyk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проведено системний аналіз відприслівникових дієслівних аналітичних синтаксичних транспозитів у структурі двоскладних та односкладних мінімальних і розширених елементарних реченнєвих конструкцій, схарактеризовано валентно зумовлені компоненти з опертям на предикативний та підрядний зв’язки; виявлено форми морфологічної експлікації підметів і керованих другорядних членів речення. The article deals with the systemic investigation of adverbialized verbal analytical syntactic transpozyts in formal-syntactic structure of simple sentence. Their typical formal-syntactic position: the position of adverbial compound predicate in two-part sentence and the position of adverbial compound principal term in composite sentence are analyzed. The role of the adverbialized verbal analytical syntactic transpozyts in two-part and composite elementary and extended elementary sentence structures are founded. The component of two-part and composite extended elementary sentence structures due to it’s valence with the bases for predictive and subordinate relationships are characterized. The forms of morphological expression of the subjects and governed subordinate members of the sentence are detected.
Adverbialized Verbal Analytical Syntactic Transpozyts in Formal-Syntactic Structure of Simple Sentence
Keywords: відприслівниковий дієслівний аналітичний синтаксичний транспозит; відприслівниковий дієслівний аналітичний напівморфологізований синтаксичний транспозит; прислівниковий складений присудок; прислівнико- вий складений головний член односкладного речення; підмет; керований другорядний член речення; adverbialized verbal analytical syntactic transpozyt; adverbialized verbal analytical semi-morphologizated syntactic transpozyt; adverbial compound predicate; adverbial compound leading term of composite sentence; subject; governed subordinate member of the sentence